The Keabsahan Talak melalui Media Sosial dalam Putusan Nomor 101/Pdt.G/2013/PAJB: Analisis Yuridis dalam Perspektif Fikih Kontemporer - Firdaus, Firdaus; Desminar, Desminar; Anggreni, Ika (AHKAM, 2025)
The increasing prevalence of divorce declarations made via social media has become a pressing issue, warranting examination from the perspectives of Indonesian positive law, the Kompilasi Hukum Islam (KHI), and contemporary fiqh interpretations. This study aims to analyze the legal validity of divorce (talak) conveyed through social media, based on these three frameworks, with reference to Case Decision Number 101/Pdt.G/2013/PA.JB. A normative juridical method was employed through library research. The findings indicate that, from a fiqh perspective, talak delivered via social media may be considered valid by analogy (qiyas) based on the legal reasoning (‘illat) as discussed by al-Mawardi. However, under Indonesian positive law, specifically Law No. 1 of 1974 Articles 38–40, Law No. 7 of 1989 in conjunction with Article 65, and Article 115 of the KHI divorce is only legally valid when pronounced before a session of the religious court. Most contemporary fiqh scholars also uphold the view that divorce must be conducted verbally and formally through legal procedures. Therefore, divorce declared through social media holds no legal validity in Indonesia. The study concludes that formal procedural compliance is essential for a divorce to be legally recognized. The implication is that married couples must exercise caution when expressing divorce declarations to avoid conflict with Islamic family law and the national legal system.